Sino-Indian Rivalry and the contemporary significance of the Indian Ocean as a zone of peace in the Asian Century - Abeysinghe, Chaminda; Wijesinghe, Hashan (Technium Social Sciences Journal, 2021)
With Asia is becoming the pivot of world affairs, the Indian Ocean is certain to become the main theatre where the great battles for world supremacy will be played. Asia’s economic success to a greater extent relies on the peace and stability of the Indian Ocean. In 1971, during the Cold War period, having realized the growing tensions in the Indian Ocean, it was declared as a Zone of Peace. However, the growing Chinese presence the Indian Ocean Region (IOR), particularly through its Belt and Road Initiative, has made India rethink of its strategy in the Indian Ocean as the country’s security is intertwined with the security of the Indian Ocean. With Sino-Indian relations have always been highly complicated to comprehend, both India and China are now competing for supremacy in the Indian Ocean for both diverse and common interests. This growing Sino-Indian rivalry in the Indian Ocean, has put the security and stability in the Indian Ocean in uncharted waters. Against this backdrop, this research attempts to examine the nature and scope of Sino-Indian rivalry in the Indian Ocean, its impact on Asia-the next global powerhouse and importance of maintaining peace and stability in the Indian Ocean to ensure continuous economic progress of the Asian region. This qualitative research is a desk study research based on both primary and secondary data. As far the findings are concerned, the interests or rather the hierarchy of the interests of China and India are different. While the main concern of China in the Indian Ocean is to secure Sea Lines of Communication (SLOC), India’s security relies on the security in the Indian Ocean. The challenge remains as to how to incorporate these diverse and conflicting challenges for mutual gain. As it stands now, this growing rivalry has significant impact on the IOR as well as the economic progress of the region. Thus, it is vital for both India and China to compromise and cooperate in order to maintain peace and stability in the region.